2016
DOI: 10.1177/0748233715590919
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA damage and DNA repair capacity in occupationally lead-exposed workers

Abstract: Occupational lead (Pb) exposure remains a significant concern for workers in Turkey. Health hazards of Pb exposure have been investigated in various test systems, but results regarding its potential genotoxic effects on exposed populations are contradictory. In this study, a control group and an exposed group were studied, each consisting of 25 male subjects. Blood lead levels (BLLs) were estimated by graphite furnace atomic absorption spectrometry. Genotoxic effects of Pb exposure were studied in leukocytes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Consistent results were shown in other studies on industry workers. [18][19][20][21][22][23][24] The analysis of the confounding factors in the above-mentioned studies is not conclusive. In this study, to evaluate the role of confounders, a multivariate regression analysis and comparisons between subgroups of smokers and nonsmokers and subgroups of subjects divided on the basis of the median age, years of work, and BMI were performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent results were shown in other studies on industry workers. [18][19][20][21][22][23][24] The analysis of the confounding factors in the above-mentioned studies is not conclusive. In this study, to evaluate the role of confounders, a multivariate regression analysis and comparisons between subgroups of smokers and nonsmokers and subgroups of subjects divided on the basis of the median age, years of work, and BMI were performed.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the other studies are difficult to compare because of the completely different demographic and epidemiological characteristics of the examined populations, the different study protocols, and the complexity of the involved pathophysiological mechanisms. [17][18][19][20][21] Additively, associations between lead exposure and DNA damage may be modified by gene polymorphisms. For instance, it has been shown that workers, who had the ALAD1-1 genotype, were more susceptible to the DNA damage development than those carrying the ALAD1-2 genotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Occupational exposure to Pb is associated with decreased repair capacity of DNA. 28 The increase in comet parameters observed at higher Pb concentrations due to prolonged exposure can be associated with less efficient and more error-prone mechanisms of repair of DNA.…”
Section: Discussionmentioning
confidence: 99%